A Comprehensive Review of the Pathogenesis, Diagnosis, and Management of Diabetic Foot Infections. (November 2021) - Mponponsuo, Kwadwo; Sibbald, R. Gary; Somayaji, Ranjani
Abstract : GENERAL PURPOSE: To review an approach to diabetic foot infections (DFIs), including acute osteomyelitis, while also discussing current practices and the challenges in diagnosis and management. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will 1. Identify the risk factors for developing DFIs. 2. Outline diagnostic techniques for assessing DFIs. 3. Select the assessment techniques that support a diagnosis of osteomyelitis. 4. Choose the appropriate pharmacologic and nonpharmacologic treatment options for patients who have DFIs. ABSTRACT: Diabetic foot ulcers result from a combination of peripheral neuropathy, vascular compromise, and repetitive trauma. Approximately 50% of individuals with diabetic foot ulcers will develop a diabetic foot infection (DFI), and 20% of individuals with a DFI will develop osteomyelitis. Herein, the authors review an approach to DFIs including acute osteomyelitis and discuss current practices and challenges in diagnosis and management. The diagnosis of a skin and soft tissue DFI is based on clinical criteria. A bone biopsy is considered the criterion standard for diagnosis of osteomyelitis; however, biopsy is not always feasible or available. Consequently, diagnosis can be made using a combination of clinical, biochemical, and radiographic findings. X-ray is the recommended imaging modality for initial evaluation; however, because of its lower relative sensitivity, advanced imaging may be used when clinical suspicion remains after negative initial testing. The microbiology of skin and soft tissue DFIs and osteomyelitis is similar. Staphylococcus aureus and other Gram-positive cocci are the most common pathogens identified. Deep cultures are preferred in both DFI and osteomyelitis to identify the etiologic pathogens implicated for targeted antimicrobial therapy. Management also requires a multidisciplinary approach. Surgical debridement in those with deep or severe infections is necessary, and surgical resection of infected bone is curative in cases of osteomyelitis. Finally, appropriate wound care is critical, and management of predisposing factors, such as peripheral neuropathy, peripheral arterial disease, tinea, and edema, aids in recovery and prevention.